Pharmacometrics in psychiatry - de Lange, Elizabeth (Henry Stewart Talks, 2015)
Psychiatric disorders, The role of genetics, Psychoactive drugs (Anxiolytics, Antidepressants & Antipsychotics), Current diagnosis & treatment, Pharmacometric approaches, Recommendations towards better treatment